2016
DOI: 10.1128/mcb.00554-15
|View full text |Cite
|
Sign up to set email alerts
|

Filamin A Expression Negatively Regulates Sphingosine-1-Phosphate-Induced NF-κB Activation in Melanoma Cells by Inhibition of Akt Signaling

Abstract: d Sphingosine-1-phosphate (S1P) is a bioactive lipid mediator that regulates many processes in inflammation and cancer. S1P is a ligand for five G-protein-coupled receptors, S1PR1 to -5, and also has important intracellular actions. Previously, we showed that intracellular S1P is involved in tumor necrosis factor alpha (TNF)-induced NF-B activation in melanoma cell lines that express filamin A (FLNA). Here, we show that extracellular S1P activates NF-B only in melanoma cells that lack FLNA. In these cells, S1P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…One possible explanation may have to do with the mutation of FLNA, the deficiency of which alters the transport of DOX via yet uncharacterized mechanisms (17). Interestingly, Campos et al (27) reported recently that FLNA negatively regulated NF-κB activation in melanoma cell by inhibition of Akt signaling, which may further link the loss-of-function mutation of FLNA to NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation may have to do with the mutation of FLNA, the deficiency of which alters the transport of DOX via yet uncharacterized mechanisms (17). Interestingly, Campos et al (27) reported recently that FLNA negatively regulated NF-κB activation in melanoma cell by inhibition of Akt signaling, which may further link the loss-of-function mutation of FLNA to NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent report showed that activation of S1PR2 in epithelial cells was crucial for elimination of neighboring cancer cells, a process known as epithelial defense against cancer (EDAC) ( 88 ). Of great interest, the process involved a gradual accumulation of Filamin A (FlnA), an actin-binding protein that we recently demonstrated to modulate S1P-induced NF-κB activation in melanoma cells ( 89 ).…”
Section: The Many Functions Of S1p In Cancermentioning
confidence: 99%
“…Receptor-mediated activation involved S1PR1/3 in different cell types ( 115 , 148 153 ). Moreover, we have recently demonstrated that activation of NF-κB by extracellular S1P in melanoma cells involved both S1PR1 and S1PR2 and was inversely correlated with the expression of the actin-binding protein FlnA ( 89 ). Interestingly, FlnA physically interacts with SphK1 ( 16 ) and TNF receptor-associated factor 2 (TRAF2) ( 154 ).…”
Section: S1p As a Modulator Of The Tumor Microenvironmentmentioning
confidence: 99%
“…Binding of S1P to SIPR1 leads to activation of NF-κB ( 79 ). It has recently been reported that S1P only activates NF-κB in M2 cells but not in FLNa bearing A7 cells suggesting that FLNa is a negative regulator of NF-κB activation ( 80 ). In the same study, it was reported that although TNFα (10 ng/ml) induced robust IκBα degradation via the proteasomal pathway in A7 cells, it had no effect on M2 cells that do not express FLNa ( 80 ).…”
Section: Discussionmentioning
confidence: 99%